Trumpeter Finch Bucanetes githagineus(M. H. C. Lichtenstein, 1823) in Kazakhstan - Fedorenko, V.A. (Fundamental and Experimental Biology, 2022)
The trumpeter finch Bucanetes githagineus (M. H.C. Lichtenstein, 1823) was first recorded for the modern territory of Kazakhstan in 1993. Over the next nearly three decades, thesedata were slightly replenished, with eight more sightings recorded, most of which belong to the territory of Mangyshlak. Although, in Mangystau, the trumpeter finch has been repeatedly recorded during the nesting period, there have been no reliable facts of its nesting in Kazakhstan until now. The article provides an overview of all the findings of the trumpeter finch for the republic, an annotation for them, as well as a map of the locations of the trumpeter finch both in Kazakhstan and in the territories of neighboring countries. As a result of fieldwork, a new location of the trumpeter finch was registered in the south of the republic: Turkistan Region, the eastern part of the Kyzylkum Desert, the Karatau mountains. Two pairs of birds were recorded. For the first time,a nest of a trumpeter finch was found on the territory of Kazakhstan. The nest was located in a niche of one of the boulders, on a rocky slope of the southeastern exposure of Karamola Mountain. The nest was under construction for a cup. Observations of its construction were carried out. Upon subsequent inspection, the nest turned out to be unfinished and abandoned. The nest was collected and placed in the collection of the Institute of Zoology of the Ministry of Education and Science of the Republic of Kazakhstan. Thus, the first data on the biology of the trumpeter finch in Kazakhstan were obtained.